Operating Cost Optimization of Electricity Distribution Network with Energy Storage - Fırış, Fatma Avli; Karadöl, İsrafil; Keçecioğlu, Ö. Fatih (Fırat University, 2024)
The aim of this study is to provide minimum operating cost by using the energy storage system at the feeder scale of the electricity distribution network with renewable and distributed energy sources. The operating optimization of the network is handled with the two-stage stochastic programming problem developed in the study. The problem was formulated with Mixed Integer Linear Programming (MILP), a linear model, through the General Algebraic Modeling System (GAMS) and solved with the CPLEX solver. In order to deal with the uncertainties in the modeling, scenario generation and reduction were carried out through Monte Carlo Simulation. Simulation studies carried out to verify the effectiveness of the proposed model were applied on IEEE-33 test busbars. Operating costs were calculated under possible grid conditions and compared among themselves according to the use of energy storage. According to the results, in cases where the energy storage system is integrated into the grid, a decrease of more than 200 dollars was observed in the operating cost in only one day's average time period compared to the cases where the storage system is not available at all. Thus, the optimum programming of energy storage with the proposed system; It has been proven to be an effective method in reducing operating costs and thus providing economic optimization, which is one of the most critical issues of power systems.

Bu çalışmanın amacı, yenilenebilir ve dağıtık enerji kaynaklarının bulunduğu elektrik dağıtım şebekesinin fider ölçeğinde enerji depolama sistemi kullanılarak minimum işletme maliyeti sağlamaktır. Şebekenin işletim optimizasyonu, çalışmada geliştirilen iki aşamalı stokastik programlama problemi ile ele alınmıştır. Problem, General Algebraic Modelling System (GAMS) aracılığıyla doğrusal bir model olan Mixed Integer Linear Programming (MILP) ile formüle edilmiş ve CPLEX çözücüsü ile çözülmüştür. Modellemedeki belirsizliklerin ele alınabilmesi için Monte Carlo Simülasyonu aracılığıyla senaryo üretimi ve azaltımı gerçekleştirilmiştir. Önerilen modelin etkinliğini doğrulamak için gerçekleştirilen simülasyon çalışmaları, IEEE-33 test baraları üzerinde uygulanmıştır. İşletme maliyetleri olası şebeke koşulları altında hesaplanmış ve kendi aralarında enerji depolamanın kullanımlarına göre karşılaştırılmıştır. Edinilen sonuçlara göre, şebekeye enerji depolama sistemi entegre edildiği durumlarda, depolama sisteminin hiç bulunmadığı durumlara göre işletme maliyetinde yalnıca bir günlük ortalama zaman periyodunda 200 doları aşkın bir düşüş gözlenmiştir. Böylece önerilen sistemle birlikte enerji depolamanın optimum şekilde programlanmasının; işletme maliyetlerini düşürmede ve dolayısıyla güç sistemlerinin en kritik konularından biri olan ekonomik optimizasyonun sağlanmasında etkin bir yöntem olduğu doğrulanmıştır.
Enerji Depolama ile Elektrik Dağıtım Şebekesinin İşletme Maliyeti Optimizasyonu
Keywords: Engineering; Mühendislik